Transformational Leadership and Lecturer Performance: The Mediating Role of Organizational Learning and Decision-Making - Nik Haryanti; Soebiantoro Soebiantoro; Engelien Yusniar Permanasari (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2025)
The main objective of this study was to examine the influence of transformational leadership, assessment, and decision-making on lecturer performance, mediated by organisational learning. Using an explanatory research design with a survey method, data were collected from 100 lecturers at Balitar Islamic University through a validated questionnaire. Data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS software. The findings indicate that transformational leadership, assessment, and decision-making have a significant direct effect on organisational learning and lecturer performance (p < 0.05). Furthermore, organisational learning also significantly influences lecturer performance. Mediation analysis revealed that organisational learning significantly mediates the relationship between assessment and decision-making and lecturer performance, but does not mediate the effect of transformational leadership. This study concludes that transformational leadership and strategic decision-making play a significant role in improving lecturer performance. The implication of this study is the importance of strengthening leadership strategies and organisational learning practices to improve the performance and sustainability of higher education institutions.